Prospective, randomized trial of bioresorbable scaffolds vs. everolimus-eluting stents in patients undergoing coronary stenting for myocardial infarction: The Intracoronary Scaffold Assessment a Randomized evaluation of Absorb in Myocardial Infarction (ISAR-Absorb MI) trial - Byrne, Robert A.; Alfonso, Fernando; Schneider, Simon; Maeng, Michael; Wiebe, Jens; Kretov, Evgeny; Bradaric, Christian; Rai, Himanshu; Cuesta, Javier; Rivero, Fernando; Hoppmann, Petra; Schlichtenmaier, Jana; et al. (European Heart Journal, 2019)
Aims Bioresorbable scaffolds (BRS) provide short-Term coronary artery scaffolding and drug delivery. Although prior trials showed a higher rate of device failure compared with conventional drug-eluting stents (DES), only a single trial investigated patients undergoing percutaneous coronary intervention (PCI) for acute myocardial infarction (MI). We aimed to compare outcomes with BRS vs. DES in patients undergoing PCI for MI. Methods and results We did a prospective, randomized, multicentre, non-inferiority, clinical trial of everolimus-eluting BRS vs. durable polymer everolimus-eluting stents (EES) in patients with acute MI. Patients were eligible for enrolment if they presented with ST-elevation MI, or non-ST-elevation MI with thrombosis visual at angiography and were randomly allocated to treatment with BRS or EES in 2:1 proportion. Angiographic follow-up was scheduled at 6-8 months and clinical follow-up was done at 12 months. The primary endpoint was percentage diameter stenosis in-segment at follow-up. A total of 262 patients were enrolled and were allocated to BRS (n = 173) or EES (n = 89). Angiographic follow-up was available for 213 (81.3%) patients. Mean diameter stenosis was 24.6 ± 12.2% with BRS vs. 27.3 ± 11.7% with EES (mean difference-2.7%, upper limit of one-sided 97.5% confidence limit 0.7%, prespecified margin of non-inferiority 5%, Pnon-inferiority <0.001). The rate of the device-oriented composite of cardiac death/target vessel MI/target lesion revascularization [BRS: 12 (7.0%) vs. EES: 6 (6.7%), hazard ratio (HR) 1.04, 95% confidence interval (CI) 0.39-2.78] and definite/probable stent thrombosis [3 (1.7%) vs. 2 (2.3%), HR 0.76, 95% CI 0.13-4.56] were comparable in both groups. Conclusion In patients undergoing PCI for acute MI BRS were non-inferior to EES for percentage diameter stenosis at angiographic follow-up. Rates of clinical events were comparable between the treatment groups, although the study was not powered to detect differences in clinical outcomes. Clinical trial registration The trial was registered at www.clinicaltrials.gov (NCT01942070).
CRIS-Team Scopus Importer:2023-03-08
Keywords: Acute myocardial infarction; Angiographic follow-up; Bioresorbable scaffold; Drug-eluting stent; Randomized clinical trial